DECISION SELECTION MODEL OF LANDING BEACH IN AMPHIBIOUS OPERATIONS EXCERCISE WITH FUZZY MCDM - Agus Setiadji; Benny Sukandari; Joni Widjayanto; Rifki Najib (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
To determine the ideal landing beaches in amphibious operations must meet the requirements / criteria that have been determined, because it serves as an important component in the choice of landing beaches. The criteria include the type of beach, gradient beach, the basic material of beach, long beach landings, the type of breaking waves, tide, the kind of obstacles beach, ocean currents, the field behind the beach, the reference point mark landing beaches and access to the exit / entrance beach , In determining the selection of the landing beaches Marine / Navy had not done the calculation / mathematical model and not using a scientific method, such instances it is necessary to make a decision-making model in the case of election of the landing beaches in amphibious operations exercise. This study aims to determine the location of the landing beachesusing Fuzzy MCDM. The use of this method is the solution to produce a more objective group decision in the selection of an amphibious landing beach which data are accurate and reliable to help solve problems that are multi-criteria. There are 11 (eleven) criteria and 4 (four) alternatives identified in this study. Of the 11 criteria which have the highest weighting criteria for the alternative chosen in the first rank third alternative, namely PPD 3. Keywords: Amphibious Operations, Fuzzy MCDM, Criteria and Alternatives.